2013
DOI: 10.3897/phytokeys.24.4375
|View full text |Cite
|
Sign up to set email alerts
|

New Lepidium (Brassicaceae) from New Zealand

Abstract: A revision of the New Zealand endemic Lepidium oleraceum and allied species is presented. Sixteen species are recognised, 10 of these are new. The new species are segregated on the basis of morphological characters supported by molecular data obtained from three DNA markers (two rDNA and one cpDNA). One species, Lepidium castellanum sp. nov., is endemic to the Kermadec Islands where it is sympatric with Lepidium oleraceum. The North Island of New Zealand supports four species, with two of them, Lepidium amissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Therefore there is no logic in excluding morphologically and ecologically distinct taxa simply because they form hybrids. Indeed, to adopt such conservative criteria would effectively eliminate a wide range of morphologically diverse and distinct, universally accepted New Zealand species in such genera as Asplenium , Celmisia , Chionochloa , Coprosma , Corokia , Elaeocarpus , Epilobium , Gaultheria , Hebe , Lepidium , Leucogenes , Leptinella , Lobelia , Melicytus , Metrosideros , Muehlenbeckia , Myrsine , Ranunculus and Sophora (Oliver 1935; Allan 1961; Franklin 1962, 1964; Rattenbury 1962; Fisher 1965; Lloyd 1972; Raven and Raven 1976; Brownsey 1977a; Given 1980b, 1984; Connor 1991; Molloy 1995; Molloy and Clarkson 1996; Heenan et al 2001; Heenan and de Lange 2004; Murray et al 2004; de Lange et al 2013a). All of the species in these genera routinely hybridise, and some can form extensive introgressive hybrid swarms.…”
Section: Charactersmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore there is no logic in excluding morphologically and ecologically distinct taxa simply because they form hybrids. Indeed, to adopt such conservative criteria would effectively eliminate a wide range of morphologically diverse and distinct, universally accepted New Zealand species in such genera as Asplenium , Celmisia , Chionochloa , Coprosma , Corokia , Elaeocarpus , Epilobium , Gaultheria , Hebe , Lepidium , Leucogenes , Leptinella , Lobelia , Melicytus , Metrosideros , Muehlenbeckia , Myrsine , Ranunculus and Sophora (Oliver 1935; Allan 1961; Franklin 1962, 1964; Rattenbury 1962; Fisher 1965; Lloyd 1972; Raven and Raven 1976; Brownsey 1977a; Given 1980b, 1984; Connor 1991; Molloy 1995; Molloy and Clarkson 1996; Heenan et al 2001; Heenan and de Lange 2004; Murray et al 2004; de Lange et al 2013a). All of the species in these genera routinely hybridise, and some can form extensive introgressive hybrid swarms.…”
Section: Charactersmentioning
confidence: 99%
“…This has meant that typification of taxa published within the Students’ Flora requires thorough examination of the exact wording used by Kirk in each instance, in conjunction with the specimens he used (in this regard see also comments with respect to the typification of Lepidium oleraceum varieties established by Kirk (1899) in de Lange et al (2013a)). Although Kirk had no type concept for his New Zealand Flora treatment, he was obviously aware of the need to indicate which specimens were representative of the taxa he was naming or treating for his flora.…”
Section: Systematicsmentioning
confidence: 99%
“…During the summer breeding season seabirds visit land regularly, so seed attachment is more likely to occur then than during winter when they are at sea for months (Furness & Monaghan 1987). Fruiting of L. oleraceum broadly coincides with the seabird breeding season (September to July;de Lange et al 2013). Maximum exposure to seawater during a single foraging trip in the breeding season would result from complete immersion for the entire duration of a foraging trip.…”
Section: Salinity Germination Effectsmentioning
confidence: 99%
“…We observed that dry seeds would readily attach to moistened surfaces and then become sticky, so wet birds may provide another attachment opportunity. Lepidium oleraceum frequently occurs at seabird burrow entrances, is used as nesting material by surface-nesting species, and is associated with sites frequented for roosting, landing or take-off (see de Lange et al 2013). The distribution of L. oleraceum within seabird colony sites suggests seabird contact with L. oleraceum seeds is highly likely.…”
Section: Seed Mucilagementioning
confidence: 99%
See 1 more Smart Citation